The effect of drug ionization on lipid-based formulations for the oral delivery of anti-psychotics - Tahlia R Meola; Kara Paxton; Paul Joyce; Hayley B Schultz; Clive A Prestidge (International Association of Physical Chemists (IAPC), 2020)
Lipid-based formulations (LBFs) are well-known to improve the oral bioavailability of poorly water-soluble drugs (PWSDs) by presenting the drug to the gastrointestinal environment in a molecularly dispersed state, thus avoiding the rate-limiting dissolution step. Risperidone and lurasidone are antipsychotics drugs which experience erratic and variable absorption, leading to a low oral bioavailability. The aim of this research was to develop and investigate the performance of risperidone and lurasidone when formulated as an emulsion and silica-lipid hybrid (SLH). Lurasidone and risperidone were dissolved in Capmul® MCM at 100% and 80% their equilibrium solubility, respectively, prior to forming a sub-micron emulsion. SLH microparticles were fabricated by spray-drying a silica stabilised sub-micron emulsion to form a solid powder. The performances of the formulations were evaluated in simulated intestinal media under digesting conditions, where the emulsion and SLH provided a 17-fold and 23-fold increase in LUR solubilisation, respectively. However, the performance of RIS was reduced by 2.2-fold when encapsulated within SLH compared to pure drug. Owing to its pKa, RIS adsorbed to the silica and thus, dissolution was significantly hindered. The results reveal that LBFs may not overcome the challenges of all PWSDs and physiochemical properties must be carefully considered when predicting drug performance.